Pengaruh Pertumbuhan Ekonomi, Pengangguran, Pengeluaran Pemerintah, dan Dana Otonomi Khusus Terhadap Tingkat Kemiskinan di Provinsi Papua Barat - Nurfaizah, Nurfaizah; Oktarina, Amimah (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
Poverty is a complex problem, therefore it is necessary to find solutions to overcome the problem. The aim of this research is to see the influence of economic growth, unemployment, and government spending and special autonomy funds (DOK) on poverty levels. This research is quantitative research using panel data regression. The data used is time series data (2017-2022 period) and cross section data (13 regencies/cities in West Papua Province). The results of this research show; GRDP has an influence on poverty with a negative relationship. The unemployment rate has no influence on poverty. The level of government spending has a significant influence on poverty with a positive relationship. The Special Autonomy Fund (DOK) has no influence on poverty.